Evolução das lesões valvares mitral e aórtica de pacientes com cardite subclínica e leve segundo avaliação dopplerecocardiográfica - Lelia Maria de Almeida Carvalho (2016)
Background: The mild rheumatic carditis (MRC) and subclinical rheumatic carditis (SRC) are basically distinguished by auscultation of mitral regurgitant murmur. The evolution of these forms is not well established in the literature. Objective: to evaluate the evolution of MRC and SRC, considering mitral and aortic insuficiency (acute phase) and regression, maintenance or worsening of these at the end of follow-up (chronic phase). Methods: Retrospective, longitudinal study, including patients with SRC and MRC. The echocardiographic evolution of mitraland aortic insuficiency was compared in both groups, considering the analysis at the end of follow-up. The chi-square test and Kaplan-Meier survival curves were used, with significance level p <0.05. Results: A total of 125 patients were included, 69 (55.2%) with SRC and 56 (44.8%) with MRC, mean age in the acute phase was 10.4 ± 2.6 years and at the end of study 19 , 9 ± 4.6 years. Follow-up time ranged from two to 23 years (mean: 9.38 ± 4.3 years). In the acute phase, mild / moderate or moderate mitral insuficiency (MI) was more frequent in patients with MRC (p = 0.001). Mild or mild / moderate aortic insuficiency (AI) was also more common in the MRC group (p = 0.045). In the chronic phase, it was observed that both MI (p <0.0001) and AI (p = 0.009) were more frequent in patients with MRC and survival free of rheumatic heart disease was higher in the SRC group (p = 0.010). Residual MI was higher in the MRC group p <0.0001) and residual AI was similar in both groups (p = 0.099).Conclusion: The resolution of MI was higher in patients withSRC and the involution of AI was less frequent and similar in both groups.